Determination of Preservative Levels of Sodium Benzoate in Packaged Mayonnaise UV-Vis Spectrophotometry as an Effort to Improve Practice Experience Basic Chemistry Course Students - Lidyawati (Jurnal Serambi Ilmu, 2024)
Sodium benzoate is the sodium salt of benzoic acid which is often used in processed foods and beverages, According to the regulation of the Head of BPOM RI No. 36 of 2013, this preservative is permitted in its use but has a limit on the use of mayonnaise, which is 1000 mg/kg body weight. The purpose of this study was to determine the content of sodium benzoate and the levels in packaged mayonnaise. This research was conducted at the Chemistry Laboratory of the Faculty of Teacher Training and Education, Syiah Kuala University, Banda Aceh to improve the student learning experience in basic chemistry courses, using five samples of packaged mayonnaise. The results showed that the five samples of packaged mayonnaise were positive for the preservative sodium benzoate. Determination of the preservative content of Sodium benzoate was determined using UV-Vis spectrophotometry method at max 280 nm. From the measurement results, the sodium benzoate content of sample M1 = 68 mg/kg, sample M2 = 35.5 mg/kg, sample M3 = 85.5 mg/kg, sample M4 = 95.5 mg/kg and M5 mg/kg = 30.5 and the use of preservative sodium benzoate in the packaged mayonnaise does not exceed the maximum limit that has been set.